Composition and Biological Activity of Vitis vinifera Winter Cane Extract on Candida Biofilm - Zdeněk Kodeš (MDPI AG, 2021)
Vitis vinifera canes are waste material of grapevine pruning and thus represent cheap source of high-value polyphenols. In view of the fact that resistance of many pathogenic microorganisms to antibiotics is a growing problem, the antimicrobial activity of plant polyphenols is studied as one of the possible approaches. We have investigated the total phenolic content, composition, antioxidant activity, and antifungal activity against Candida biofilm of an extract from winter canes and a commercially available extract from blue grapes. Light microscopy and confocal microscopy imaging as well as crystal violet staining were used to quantify and visualize the biofilm. We found a decrease in cell adhesion to the surface depending on the concentration of resveratrol in the cane extract. The biofilm formation was observed as metabolic activity of Candida albicans, Candida parapsilosis and Candida krusei biofilm cells and the minimum biofilm inhibitory concentrations were determined. The highest inhibition of metabolic activity was observed in Candida albicans biofilm after treatment with the cane extract (30 mg/L) and blue grape extract (50 mg/L). The composition of cane extract was analyzed and found to be comparatively different from blue grape extract. In addition, the content of total phenolic groups in cane extract was three-times higher (12.75 gGA/L). The results showed that cane extract was more effective in preventing biofilm formation than blue grape extract and winter canes have proven to be a potential source of polyphenols for antimicrobial and antibiofilm treatment.